Evaluation of groundwater usage in relationship to groundwater vulnerability to sea water intrusion in Cilacap Coastal - Nugrahaeni Salsabiila Bayu (EDP Sciences, 2021)
Besides being able to cause land subsidence, excessive groundwater use in coastal areas can also cause to sea water intrusion. The purpose of this study is to evaluate the use of groundwater in the study area in relation to its vulnerability to sea water intrusion. Because groundwater in the study area is used for domestic, industry and livestock purposes, the water use that is taken into account is the use of water for the three sectors. The amount of water used for domestic purposes is calculated based on the population and the amount of water needed of each person per day. The amount of water use for industry is calculated based on the number of industrial employees and water usage of each employee per day. Water use for livestock is calculated based on the number of livestock and water use of each livestock per day. The results of this water usage calculation are then linked to the criteria for groundwater vulnerability to sea water intrusion and the depth of the interface. Observing the relationship between groundwater usage and the vulnerability of groundwater to sea water intrusion and the depth of its interface, Tegal Kamulyan, Cilacap and Sidakaya villages, all of which are located in South Cilacap District, need attention. The three village are classified as moderate vulnerability to sea water intrusion and shallow interface depth, but their water usage is quite high. For this reason, it is necessary to make efforts to find other water sources for domestic, industry and livestock requirement other than groundwater.